Penggunaan Media Pembelajaran Yang Efektif Secara Daring pada Mata Pelajaran Rangkaian Listrik - Saseno Muhammad Saseno; Muhammad Malik Ridwan; Muhammad Rafi Alfarizi; Muhammad Irfan Maulana; Lutfi Zulfikar (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2023)
In the present time, online-based learning has become an integral part of modern education, thanks to the advancements in information and communication technology that cannot be denied. However, there are several challenges that have emerged, particularly in the past two years. The global COVID pandemic has necessitated the implementation of online learning. In designing this form of learning, there are several factors that need to be considered. This article will discuss the effectiveness of online learning.